Handbook of Resilience in Children - Goldstein, Sam.; Goldstein, Sam.; Brooks, Robert B.; Brooks, Robert B. (Springer US : Imprint: Springer, 2013)
Today’s children face a multitude of pressures, from the everyday challenges of life to the increasing threats of poverty, exploitation, and trauma. Central to growing up successfully is learning to deal with stress, endure hardships, and thrive despite adversity. Resilience – the ability to cope with and overcome life’s difficulties – is a quality that can potentially be nurtured in all young people. The second edition of the Handbook of Resilience in Children updates and expands on its original focus of resilience in children who overcome adversity to include its development in those not considered at risk, leading to better outcomes for all children across the lifespan. Expert contributors examine resilience in relation to environmental stressors, as a phenomenon in child and adolescent disorders, and as a means toward positive adaptation into adulthood. New and revised chapters explore strategies for developing resilience in the family, the therapist’s office, and the school as well as its nurturance in caregivers and teachers. Topics addressed include: Resilience in maltreated children and adults. Resilience and self-control impairment. Relational resilience in young and adolescent girls. Asset-building as an essential component of treatment. Assessment of social and emotional competencies related to resilience. Building resilience through school bullying prevention programs. Large-scale longitudinal studies on resilience. The second edition of the Handbook of Resilience in Children is a must-have reference for researchers, clinicians, allied practitioners and professionals, and graduate students in school and clinical psychology, education, pediatrics, psychiatry, social work, school counseling, and public health.